Recombinant avian metapneumovirus subtype C expressing HA protein of H9N2 avian influenza virus are stable and induce protection - Guo, Yu; Cheng, Jing; Zhang, Shuai; Zhang, Yuanyuan; Zuo, Yuzhu; Liu, Tao; Wang, Yun; Yang, Chun; Cheng, Chunjie; Fan, Jinghui; Jiang, Haijun (Frontiers in Microbiology, 2024)
To prevent H9N2 avian influenza virus (AIV) and Avian metapneumonovirus/C (aMPV/C) infections, we constructed recombinant aMPV/C viruses expressing the HA protein of H9N2 AIV. In addition, EGFP was inserted into the intermediate non-coding region of P-M protein in the aMPV/C genome using a reverse genetic system. The conditions for rescuing the recombinant virus were enhanced followed by insertion of the H9N2 AIV HA gene into the same location in the aMPV/C. The constructed recombinant virus raMPV/C-HA expressed the H9N2 AIV HA protein and showed good stability. Immunization of chicks with raMPV/C-HA increased the generation of neutralizing antibodies against aMPV and H9N2 AIV for 21 days. In the late challenge experiment, raMPV/C-HA effectively inhibited the replication of the virus in vivo, decreased the incidence of infection and conferred protection effects.